Aktivasi dan Tingkat Perkembangan Embrio Partenogenetik Mencit Setelah Dipapar Calcimycin dan Ionomicyn (ACTIVATION AND DEVELOPMENT RATE OF MICE PARTHENOGENETIC EMBRYOS EXPOSURED IN CALCIMYCIN AND IONOMICYN) - Nalley, Wilmientje Marlene; Hine, Thomas Mata (Jurnal Veteriner; Vol 16 No 4 (2015), 2016)
The aim of study was to find out the best concentration and exposure time of calcimycin andionomycin in order to produce parthenogenetic embryos. Female Swiss Webster mice were fisrtlyprimed with Pregnant Mare’s Serum Gonadotropin (PMSG) and Human Chorionic Gonadotropin (hCG)with an interval of 48 hours. Sixteen hours after injection of hCG oocyte was collected by Dulbecco’sPhosphate Buffer Saline (dPBS) as a flushing medium. To separate the eggs from cumulus cells wereused hyaluronidase enzyme. The good quality oocytes were incubated in activation medium that isionomycin or calcimycin with a concentration of 3, 6, or 9 ìM and exposure time 1, 4, or 7 minutes. Toyield diploid embryos were used 5 ?g/ml cytochlasin B for four hours at 37°C, 5% CO2. Activatedoocytes characterized by the formation of pronuclei washed three times in Potassium SimplexOptimization Medium (KSOM) and subsequently cultured in the same medium until blastocyst stage.The results showed that oocytes activated at calcimycin, the best results was presented at concentration6 ?M and exposure time four minutes, i.e. activation rate reached 96%, cleavage rate 82% and blastocystrate 28%. On the other hand, oocytes activated in ionomycin, the best results was presented atconcentration 3 ?M and exposure time four minutes, i.e. activation rate reached 82%, cleavage rate64% and blastocyst rate of 4%. It was concluded that the best concentration and exposure timecalcimycin on mice oocytes were 6 ?M for four minutes, whereas ionomycin were 3 ?M for four minutes.
Keywords: mice parthenogenetic embryos, activation, development, calcimycin, ionomycin